RESISTING PATRIARCHY IN FEUDAL JAPAN THROUGH WOMEN’S AGENCY IN SHOGUN (2024) - Farah Nabila Anansyah; Rahayu Puji Haryanti (Lire Journal (Journal of Linguistics and Literature), 2025)
This study examines the forms of resistance by female characters against patriarchal culture in the television series Sh?gun (2024). The study highlights how feudal Japanese society shaped gender roles, and how Lady Mariko, as the main female protagonist, negotiated her agency within a strong patriarchal system. Using Simone de Beauvoir's existentialist feminism theory and Sylvia Walby's concept of patriarchy, this research analyzes intellectualism, self-sacrifice, and strategic compliance as means of subverting social norms. Through qualitative methods involving in-depth understanding and character analysis, this study identifies that Mariko's form of resistance manifests through measured actions against social expectations, codes of honor, and gender-based power hierarchies. The findings show that instead of engaging in open rebellion, Mariko demonstrates agency through symbolic intelligence and self-sacrifice as a challenge to male dominance. This research also highlights how the series reconstructs historical narratives by placing women's inner strength and intelligence at the center of political and cultural stories. This study contributes to feminist criticism of popular media by showing that contemporary historical dramas can present representations of women's resistance within patriarchal systems and reimagine women's positions as active agents in male-dominated history. This research reinforces the ongoing discourse on gender, power, and representation in popular culture, emphasizing that agency within oppressive systems often emerges through subtle, complex, and contextually bound forms of resistance.